2002
DOI: 10.1002/1099-0682(200207)2002:7<1677::aid-ejic1677>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Novel Series of Organometallic Merocyanines Combining the Potent Electron-Donating [(CpFeCO)2(μ-CO)(μ-C=CH−)] Fragment with Tropylium-Type Acceptors

Abstract: The potent electron‐donating group [(CpFeCO)2(µ‐CO)(µ‐C=CH−)] was combined with different tropylium‐based acceptors yielding the push‐pull complexes [(CpFeCO)2(µ‐CO)(µ‐C=CH−CH=A)][BF4] where =A represents [=CH−(η7‐C7H6)Cr(CO)3]+ (5), [={C10H7}]+ (azulenylium) (7) [={C10H4Me2iPr}]+ (guaiazulenylium) (8). Crystal structures of the precursor complexes [(CpFeCO)2(µ‐CO)(µ‐C=CH−CH=CH−C7H7)] (3), [(CpFeCO)2(µ‐CO){µ‐C=CH−CH=CH−(η6‐C7H7)Cr(CO)3}] (4) and the push‐pull derivative 5 are presented. Whereas complexes 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…These results seem to indicate that NMR spectroscopic data might be used to give an insight of the role played by the organometallic fragment on the first hyperpolarizability response of complexes containing the same chromophore. Within the same scope to relate NMR spectroscopic parameters with first hyperpolarizabilities, other authors reported a correlation between 1 H-1 H coupling constants and the first hyperpolarizability of organometallic merocyanines [27]. The linear trend found in this work can be useful to predict first hyperpolarizabilities of other monocyclopentadienylmetal complexes containing p-NCC 6 H 4 NO 2 or p-NC(C 6 H 4 ) 2 NO 2 chromophores if the degree of electronic communication between the corresponding organometallic fragment and nitrile derivatives is known.…”
Section: Resultsmentioning
confidence: 99%
“…These results seem to indicate that NMR spectroscopic data might be used to give an insight of the role played by the organometallic fragment on the first hyperpolarizability response of complexes containing the same chromophore. Within the same scope to relate NMR spectroscopic parameters with first hyperpolarizabilities, other authors reported a correlation between 1 H-1 H coupling constants and the first hyperpolarizability of organometallic merocyanines [27]. The linear trend found in this work can be useful to predict first hyperpolarizabilities of other monocyclopentadienylmetal complexes containing p-NCC 6 H 4 NO 2 or p-NC(C 6 H 4 ) 2 NO 2 chromophores if the degree of electronic communication between the corresponding organometallic fragment and nitrile derivatives is known.…”
Section: Resultsmentioning
confidence: 99%
“…At zero TFA concentration, the polymer exhibits two strong absorption bands at 238 and 386 nm in the UV region of the spectrum associated with the π-π* transition of the thiophene ring and the azulene moiety, respectively. Upon addition of TFA, a new band at 694 nm was observed which was attributed to the formation of azulenium cation radicals 16,17 (refer to later discussion on the EPR study). In fact, an increase in the TFA concentration (<30%, v/v) and a rise in absorbance in intensity of the band at 694 nm (1.78 eV) are concomitant with a gradual bleaching of the π-π* transition band at 386 nm.…”
mentioning
confidence: 96%
“…After filtering the reaction mixture and overlaying the filtrate with diethyl ether, the air‐stable merocyanine salts 195 and 196 were separated (Scheme 71). [ 108 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
“…The hyper‐Rayleigh scattering (HRS) tests were successful in determining the nonlinear optical characteristics of 196 , and the lesser β0 value may be explained by a smaller bond length variation even though the guaiazulenylium cation is a much stronger electron acceptor. [ 108 ]…”
Section: Functionalization Of Azulene Through Metal‐catalyzed Cross‐c...mentioning
confidence: 99%
See 1 more Smart Citation